Factors Influencing the Growth of Multiple Intelligences in Children Aged 0 to 5 Years: A Focused Study in Northeastern India - Ailani, Mohit (Global journal of Business and Integral Security, 2025)
This paper explores the development of multiple intelligences (MI) in early childhood, focusing on children aged 0 to 5 years in the Northeastern region of India. This study investigates the factors influencing the growth of multiple intelligences in children utilizing a mixed-methods approach to provide a comprehensive understanding of this developmental stage. The research combines quantitative data collected through standardized assessments of children's intelligences and demographic surveys with qualitative insights gathered from interviews and focus group discussions with parents, educators, and child development specialists. The findings reveal that various socio-cultural, environmental, and educational factors significantly impact the development of multiple intelligences in early childhood. Key influences identified include parental involvement and educational practices, access to resources and learning materials, cultural values emphasizing certain intelligences, and the role of community support systems. The study highlights the importance of a nurturing environment that fosters diverse learning experiences, which are crucial for holistic development. Additionally, the research underscores the need for tailored educational strategies that recognize and cultivate different intelligences among children to promote their overall growth. By addressing the unique challenges and opportunities present in the northeastern region of India, this study aims to inform policymakers, educators, and parents about effective practices that can enhance the developmental outcomes for young children, thereby contributing to the broader discourse on early childhood education and development in diverse cultural contexts.